O uso da informação contábil como instrumento de gestão nas micro e pequenas empresas do município de Alegrete/RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This study has as its theme the use of accounting information as a management tool in the micro and small companies of the municipality of Alegrete/RS. Has as specific objectives: to demonstrate what are the information provided by municipal accounting professionals, to identify the characteristics of accounting information and its use for decision making and to evaluate the perception of business and accounting professionals on the importance of the demonstrations accounting in the process of management of micro and small enterprises located in the municipality. This study is characterized as a descriptive research, with a focus on document analysis and support in qualitative approach, the basis of the work was given by bibliographical research through surveys involving the subject under study, as well as semi-structured interviews with accounting and micro professionals and small business owners in the city of Alegrete / RS. By analyzing the results, it was evident that there is a disagreement as to the opinion of the respondents regarding the information provided by professional accounting and received by micro and small business, demonstrating that most business owners unaware of the full potential of information professionals accounting have to offer. The analysis also shows that the majority of micro and small entrepreneurs interviewed do not usually use accounting information as a basis for making decisions. Although respondents mostly recognize the credibility and importance of the information generated through the financial statements they replace them often for internal controls, turning the accounting mere executor of tax and labor obligations. This finding is also evidenced when unanimously, business and financial professionals say the service legal and tax the company is among the main tasks of bookkeeping, a detour in the real aim of Accounting Science.
Keywords: Engenharia econômica; Microempresas; Pequenas empresas; Informações contábeis; Gestão empresarial; Economic engineering; Microenterprises; Small business; Accounting information; Business management; CNPQ::ENGENHARIAS